On-the-fly laser machining: a case study for in situ balancing of rotative parts - Stoesslein, M.; Axinte, Dragos A.; Gilbert, D. (American Society of Mechanical Engineers, 2016)
On-the-fly laser machining is defined as a process that aims to generate pockets/patches on target components that are rotated or moved at a constant velocity. Since it is a nonintegrated process (i.e., linear/rotary stage system moving the part is independent of that of the laser), it can be deployed to/into large industrial installations to perform in situ machining, i.e., without the need of disassembly. This allows a high degree of flexibility in its applications (e.g., balancing) and can result in significant cost savings for the user (e.g., no dis(assembly) cost). This paper introduces the concept of on-the-fly laser machining encompassing models for generating user-defined ablated features as well as error budgeting to understand the sources of errors on this highly dynamic process. Additionally, the paper presents laser pulse placement strategies aimed at increasing the surface finish of the targeted component by reducing the area surface roughness that are possible for on-the-fly laser machining. The overall concept was validated by balancing a rotor system through ablation of different pocket shapes by the use of a Yb:YAG pulsed fiber laser. In this respect, first, two different laser pulse placement strategies (square and hexagonal) were introduced in this research and have been validated on Inconel 718 target material; thus, it was concluded that hexagonal pulse placement reduces surface roughness by up to 17% compared to the traditional square laser pulse placement. The concept of on-the-fly laser machining has been validated by ablating two different features (4 × 60 mm and 12 × 4 mm) on a rotative target part at constant speed (100 rpm and 86 rpm) with the scope of being balanced. The mass removal of the ablated features to enable online balancing has been achieved within < 4 mg of the predicted value. Additionally, the error modeling revealed that most of the uncertainties in the dimensions of the feature/pocket originate from the stability of the rotor speed, which led to the conclusion that for the same mass of material to be removed it is advisable to ablate features (pockets) with longer circumferential dimensions, i.e., stretched and shallower pockets rather than compact and deep.